The Effect of Profitability, Corporate Governance, Corporate Social Responsibility and Company Size on Tax Avoidance: Pengaruh Profitabilitas,Corporate Governance,Corporate Social Resposibility dan Ukuran Perusahaan Terhadap Tax Avoidance - Eva Fransisca Diah Trisnawati; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2021)
Tax Avoidance is a strategy undertaken by every company in tax avoidance that can be measured using the cas effective tax rate (CETR). The purpose of this study was to determine the effect of Profitability, Corporate Governance, Corporate Social Responsibility, and company size on Tax Avoidance. In this study, the population used is property companies listed on the Indonesia Stock Exchange for the period 2016 to 2018. The method of determining the sample in this study uses the purposive sampling method so that a total sample of 27 property companies is obtained. The data in this study were analyzed to examine the effect of each variable on tax avoidance using multiple linear regression analysis and simultaneously on tax avoidance. Empirical evidence shows that the results of the analysis of firm size have no significant effect on tax avoidance. As for Profitability, Corporate Governance, Corporate Social Responsibility have an influence on tax avoidance. The benefit of this research is to add to the literature related to Tax Avoidance issues and to support previous research. Keywords: Tax Avoidance, Profitability, Corporate Governance, Corporate Social Responsibility and Company Size.